2015
DOI: 10.1108/ijcst-01-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the performance of a PCM cooling vest considering its side effects

Abstract: Purpose – The purpose of this paper is to identify and evaluate the potential cooling contribution provided by a phase change material cooling vest as part of the total heat exchange mechanism of the body and take in to account the negative side effects of wearing the cooling garments. Design/methodology/approach – In this study, the three-part system of body-garment-environment has been simulated through the finite element method and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Modeling the use of the cooling garment on the body is a method by which we can study the heat exchange between the cooling garment and the body as well as the surrounding environment. The authors of the present paper have already conducted relevant and appropriate evaluation of the effects of the cooling garment on the body and heat exchange of a system having the three parts of body, cooling garment, and the environment using software simulation [21,22]. So, it has been attempted in this study to investigate the efficiency of the cooling garment as a function of its ability to absorb the body's heat.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the use of the cooling garment on the body is a method by which we can study the heat exchange between the cooling garment and the body as well as the surrounding environment. The authors of the present paper have already conducted relevant and appropriate evaluation of the effects of the cooling garment on the body and heat exchange of a system having the three parts of body, cooling garment, and the environment using software simulation [21,22]. So, it has been attempted in this study to investigate the efficiency of the cooling garment as a function of its ability to absorb the body's heat.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate increase in weight of CPC over a short period of time would have intensified the cardiovascular strain, but had less impact on core temperature and mean skin temperature. YAZDI et al [44] showed that an increase in the weight of CPC caused an increase in metabolism. DORMAN et al [4] developed a slope regression line based on human experiments, showing a 2.7% increase in metabolic rate for each additional kilogram of clothing weight.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although IZI and SMART vests provided lower Re (%), their C values were also significantly lower compared to other tested evaporative vests. The vests with PCM inserts also reduced the evaporative capacity of the observed system, presumably due to reduced breathability of the materials (Mokhtari Yazdi et al 2015), with findings suggesting their efficiency would be greater compared to others in humid environments, where evaporative cooling is reduced or when wearing the vests underneath unbreathable protective clothing (Maley et al 2020).…”
Section: Thermal Resistance (Rt) and Relative Evaporative Resistance mentioning
confidence: 95%